Volumetric laser endomicroscopy in Barrett's esophagus: a feasibility study on histological correlation. Issue 6 (1st September 2016) - Swager, A.; Boerwinkel, D. F.; de Bruin, D. M.; Weusten, B. L.; Faber, D. J.; Meijer, S. L.; van Leeuwen, T. G.; Curvers, W. L.; Bergman, J. J.
Summary: Volumetric laser endomicroscopy (VLE) is a novel balloon-based optical coherence tomography (OCT) imaging technique that may improve detection of early neoplasia in Barrett's esophagus (BE). Most OCT studies lack a direct correlation between histology and OCT images. The aim is to investigate the optimal approach for achieving one-to-one correlation of ex-vivo VLE images of endoscopic resection (ER) specimens with histology. BE patients with and without early neoplasia underwent ER after delineating areas with electrocoagulation markers (ECM). After ER, specimens underwent additional ex-vivo marking with several different markers (ink, pin, Gold Probe) followed by ex-vivo VLE scanning. ER specimens were carefully sectioned into tissue blocks guided by the markers. Histology and VLE slides were considered a match if ≥ 2 markers were visible on both modalities and mucosal patterns aside from these markers matched on both histology and VLE. From 16 ER specimens 120 tissue blocks were sectioned of which 23 contained multiple markers. Fourteen histology–VLE matches were identified. ECMs and ink markers proved to be the most effective combination for matching. The last 6/16 ER specimens yielded 9/14 matches, demonstrating a learning curve due to methodological improvements in marker placement and tissue block sectioning. One-to-one correlation of VLE and histology is complex but feasible. The groundwork laid in this study will provide high-quality histology–VLE correlations that will allow further research on VLE features of early neoplasia in BE.